Mobility-aware Offloading Decision For Multi-access Edge Computing In 5g Networks - Saeid Jahandar; Lida Kouhalvandi; Ibraheem Shayea; Mustafa Ergen; Marwan Hadri Azmi; Hafizal Mohamad (MDPI, 2024)
Indexed by WOS/Scopus/ERA